Islamic Education Landscape: A Bibliometric Analysis of Pesantren Institutions - Luthfi Fitria Dewi; Mohammad Zakki Azani; Muhamad Subhi Apriantoro; Afief El Ashfahany; Humairah Minin (AL-FIKRA, 2023)
This study aims to describe the development map and research direction of Islamic education and pesantren in Indonesia in publications indexed by the Scopus database. This study uses bibliometric analysis techniques to explore all publications indexed in the Scopus database on Islamic education and pesantren in Indonesia from 1966 to 2023. The data obtained were analyzed using Microsoft Excel and R/R-Studio. Vosviewer is used to visually analyze keyword occurrence and document citation stimulants. The author found 957 publications that fit the function, subject, and criteria set. The results of this study show that research with the theme of Islamic education and pesantren in Indonesia is the most researched in 2021. Indonesia is the country that contributes the most publications followed by Malaysia as the country that publishes the most in second place. The highest affiliation is occupied by the University Kebangsaan Malaysia. While the most relevant author is Hamzah, M.I. The limitation of this study is only taking data sets or metadata in publications indexed by Scopus. Other national and international databases were not taken into account in the study. This study presents a brief overview of the literature accessible to researchers working in education and provides recommendations for future research. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//